Judicial Activism vs. Electoral Justice: The Overlooked Purcell Principle in Indonesia - Nugroho, Rahmat Muhajir; Gymnastiar, Reyhan; Sobirin, Sobirin (Fakultas Hukum Universitas Islam Indonesia, 2025)
The constitutional dilemma surrounding the authority of the Constitutional Court to review electoral laws during an ongoing election cycle reflects the complex tension between the protection of rights and the maintenance of legal order. The Constitutional Court’s judicial activism, particularly when issuing landmark rulings close to or during electoral stages, often intensifies what constitutional law scholars refer to as the counter-majoritarian difficulty—a legitimacy problem that arises when a non-majoritarian judicial body invalidates laws enacted by democratically elected institutions. In this context, the Purcell Principle, a judicial restraint doctrine developed by the United States. Supreme Court, offers an important framework to prevent last-minute changes to electoral regulations that may cause legal uncertainty and confusion among voters. However, directly transplanting this principle into Indonesia is problematic due to significant differences in legal systems, institutional structures, and the fragmented nature of its democratic processes. To address this challenge, this article proposes an adaptive concept called the limited Purcell principle, comprising four key pillars: (1) temporal limitation on the Constitutional Court’s rulings during the election period; (2) postponement of the implementation of rulings which have fundamental legal consequences; (3) exceptions to safeguard the constitutional rights of citizens; and (4) screening mechanisms during the preliminary examination phase. This model aims to strike a balance between protecting constitutional rights and ensuring electoral stability, while encouraging the Constitutional Court to exercise its constitutional mandate more prudently and proportionally within the framework of Indonesia’s constitutional democracy.